How Accurate is it to Define Biofuels as Renewable Energy? A Theoretical and Empirical Analysis - Karacan, Rıdvan; Baris, Ismail; Yardimci, M. Emin; Cengiz, Vedat (International Journal of Energy Economics and Policy, 2021)
Currently, energy needs are largely provided from fossil fuels. However, fossil fuels, which have a history of about two hundred years, tend to run out every day. On the other hand, the human population is growing rapidly. In this context, it is of great importance that the resources to meet the energy needs of the growing population are sustainable. Energy sources that meet this definition have entered the literature as “renewable energy”. In the current literature, biofuels are defined as renewable energy sources. Yet, biofuels are fuels of biological origin that depend on agricultural production. Further biofuel production takes place at the expense of the use of land allocated for food production. The reduction of land allocated to food production can directly affect the prices of agricultural products. Therefore, interest in biofuel production has decreased. Is it right to accept biofuels as renewable energy in this form? Our goal is to contribute to the literature by revealing a mistake that is known to be true. For this purpose, both theoretical and empirical analyses were conducted based on “biofuel production” and “agri-food prices”. The United States, the world's largest producer of biofuels, was selected for empirical analysis. In this context, the ARDL model of long-term and short-term relationships between variables was decoded using data containing 1992-2017. The findings revealed the existence of a long-term linear relationship between the two variables. Keywords: Biofuels, Agri-Food Prices, Renewable Energy. JEL Classifications: C1, Q4, Q3 DOI: https://doi.org/10.32479/ijeep.11935